Religious Attitudes and Radical Behavior of Islamic Boarding School Students - Sarbini Sarbini; Moh. Dulkiah (Psympathic : Jurnal Ilmiah Psikologi, 2022)
Previous studies on radicalism among Islamic school students mostly focused on those residing in boarding schools. However, some students did not reside in the boarding school but usually participated in radicalism as "non-resident students". This study aimed to examine the influence of religious attitudes on radical behavior among non-resident students. A quantitative correlational approach was used and involved 100 subjects aged 12-20 years from 10 boarding schools in Cirebon Regency, West Java. The results showed that religious attitudes significantly influenced radical behavior of non-resident students, with a contribution of 32%.